Contested Records : The Turn to Documents in Contemporary North American Poetry - Leong, Michael (Book collections on Project MUSE., 2020)
"Why have so many contemporary poets turned to source material, from newspapers to governmental records, as inspiration for their poetry? How can citational poems offer a means of social engagement? What are the advantages and perils of appropriating text? Synthesizing research in cultural memory studies, art history, public sphere theory, and the history of the humanities, Michael Leong answers such questions as he argues that poems driven by the remixing and reframing of found texts powerfully engage with the collective ways we remember, forget, and remember again. Going well beyond Wordsworthian recollections in tranquility, authors of such research-driven and mnemotechnic work use previous inscriptions as a springboard into public intellectualism This is the first book-length study to examine conceptual writing and documentary poetry under the same cover, showing how diverse writers associated with different poetry communities have a common interest in documentation. Putting into provocative conversation writers such as Amiri Baraka, Kenneth Goldsmith, R.B. Kitaj, Mark Nowak, M. NourbeSe Philip, Vanessa Place, and Claudia Rankine, Leong analyzes a range of twenty-first-century poems that have been reviled, celebrated, or in some cases met with equally telling indifference. In doing so, Leong offers nuanced and non-polemical treatments of some of the most controversial debates about race and ethnicity in twenty-first century literary culture. Situating his objects of study within the wider context of the humanities, Leong's Extending the Document in Contemporary North American Poetry suggests nothing less than a continual extension of our conceptions of poetry"--